The Microstructure of Egg Shell Waste Treated with H3PO4, In vitro Solubility in Different Particle Size and the Using Effect on the Egg Shell Quality of Laying Hens - Kismiati , Sri; Yuwanta, Tri; Zuprizal; Supadmo (International Journal of Poultry Science, 2013)
The aim of the research was to study the microstructure changes of egg shell waste treated with H3PO4 and its effect on in vitro solubility and egg shell quality of laying hens. Egg shell waste was soaked in water with the temperature of 80°C, drained and divided into 4 parts. Part 1 was sun dried (control), part 2 was soaked in H3PO4 3%, part 3 was soaked in H3PO4 4% and part 4 was soaked in H3PO4 5%. Furthermore, egg shells were drained, sun dried and then grinded to a particle size of 1 and 3 mm and used in the feed of laying hens. A total of 96 twenty-five weeks old of laying hens (ISA Brown strain) were divided into 8 experimental dietary treatment in 4 x 2 factorial arrangements with 3 replication. Results of the research showed that the concentration of H3PO4 effected on egg shell microstructure changes and interaction of H3PO4 3 and 4% and particle size 1 mm was increased in vitro solubility. Concentration of H3PO4 and particle size had not significantly effect (P>0.05) on calcium intake, egg shell weight and egg shell percentage but significantly effect (P<0.05) on phosphorus intake and egg shell thickness. Egg shell thickness was increased at H3PO4 5% and particle size 3 mm. The research concluded that H3PO4 resulted in microstructure changes and in vitro solubility but did not change the quality of the egg shell, except egg shell thickness.